1999
DOI: 10.1111/j.1469-1795.1999.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of domestic cattle hybrids in wild cattle and bison species: a general approach using mtDNA markers and the parametric bootstrap

Abstract: Many species are currently undergoing reductions in population size due to widespread habitat loss and expanding human activities. Because interspecific hybridization is often a consequence of population decline and fragmentation, identification of individuals or populations with hybrid ancestry is an increasingly important issue in conservation biology. In many wild cattle and bison species, the problem of natural hybridization has been compounded by indiscriminate crossbreeding with domestic cattle for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 32 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…In this study, we first chose a cattle-specific mtDNA control region fragment ( Ward et al 1999 ) and cattle-specific alleles at three autosomal microsatellite loci ( ILSTS013 , ILSTS050 and SPS115 ) for a diagnostic approach to assess the impact of cattle introgression on domestic yak populations. We also chose an estimator of admixture proportion and a model-based Bayesian admixture analysis, two methods that have been widely used for estimating the admixture proportion between closely related species ( Hanotte et al 2002 ; Freeman et al 2004 ; Edwards et al 2007 ), in order to estimate cattle admixture proportion in the yak genetic pool at the genome level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we first chose a cattle-specific mtDNA control region fragment ( Ward et al 1999 ) and cattle-specific alleles at three autosomal microsatellite loci ( ILSTS013 , ILSTS050 and SPS115 ) for a diagnostic approach to assess the impact of cattle introgression on domestic yak populations. We also chose an estimator of admixture proportion and a model-based Bayesian admixture analysis, two methods that have been widely used for estimating the admixture proportion between closely related species ( Hanotte et al 2002 ; Freeman et al 2004 ; Edwards et al 2007 ), in order to estimate cattle admixture proportion in the yak genetic pool at the genome level.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle mtDNA in yak was detected through the amplification of a 357-bp taurine and indicine cattle-specific mtDNA control region fragments using primers MTD1 (5′-AGCTAACATAACACGCCCATAC-3′) and MTD2 (5′-CCTGAAGAAAGAACCAGATGC-3′) ( Ward et al 1999 ) in a multiplex PCR reaction also containing primers MTR1 (5′-CCCGCCTGTTTATCAAAAACAT-3′) and MTR2 (5′-CCCTCCGGTTTGAACTCAGAT-3′) ( Derr et al 1992 ), which amplified a 590-bp mammalian-conserved 16S rDNA fragment as an internal control. The partial mtDNA control region fragment was further sequenced for cattle-specific mtDNA detected in yak populations to verify their taurine or indicine identities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility for this finding may also be explained by hybridisation between another closely related species. A previous study from the labs of University Station in Texas also found an anomalous association between Yak and Taurine cattle, due to an animal descending from a B. indicus cow [ 5 , 9 , 11 ]. The fact that a Bos indicus sample was not included in the data set, meant tests could not determine if some of the aberrant sites in our sample were due to gene flow between B. grunniens and B. indicus and this will need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, several bovines have been domesticated, namely water buffalo (Bubalus bubalis), yak (Bos grunniens), gaur (Bos gaurus), and banteng (Bos javanicus) (Guo et al, 2006;Kumar et al, 2007;Machugh, 1996). Yak, gaur and banteng are closely related to B. taurus and B. indicus (Decker et al, 2009), and mitochondrial data indicates some admixture between Asian cattle and yaks (Kikkawa et al, 2003;Ward et al, 1999). Other molecular data indicates mixing between Asian cattle and banteng.…”
Section: The Dawn Of De-extinctionmentioning
confidence: 99%